Risk Factors Modifying the Parameters of Volumetric Sphygmography (A Literature Review) - Rudoi, M.D.; Makarova, E.V.; Troshin, V.V. (Juvenis Scientia)
Volumetric sphygmography is a functional diagnostic method that makes it possible to obtain multiple indicators reflecting the current state of the cardiovascular system in a short time. The methodology is relatively simple, does not require significant time or costly materials, and can be carried out by general medical staff. The primary parameter of sphygmography — recognized by both Russian and international experts as an integral marker of vascular-wall health — is the cardio-ankle vascular index (CAVI). CAVI reflects arterial rigidity and is directly proportional to the biological age of blood vessels. This literature review presents the latest data on factors that can modify vascular-wall stiffness. It describes how vascular stiffness and arterial biological age change under the influence of sex, age, disturbances of carbohydrate and lipid metabolism, chronic kidney disease, hypertension, smoking, overweight, atherosclerotic cardiovascular diseases of various localizations, infectious diseases, and the use of antihypertensive or lipid-lowering therapies. The review may be useful both for practitioners evaluating a patient’s cardiovascular risk and for researchers planning to use volumetric sphygmography in their studies.